(untitled) (Global Journal of Science Frontier Research, 2018)
In the article is introduced the concept of scalarvector written Lagrange’s function for the moving charge. This procedure of the introduction to of Lagrange the moving charge earlier is not Lagrangian of fixed charge, which is fo charges.